Factores Asociados al uso del Cigarrillo en Estudios del Recinto de Ciencias Médicas, Universidad de Puerto Rico - Vélez-González, Nardy I.; Vázquez-García, Virginia; Dávila-Torres, René R.; Colón-Colón, Marcilyn (Puerto Rico Health Sciences Journal, 2012)
see manuscript